The obesity paradox in patients with acute coronary syndromes – is it still applicable to the current era? The ACSIS registry 2000–2018. (3rd October 2022) - Gurevitz, C; Mohsen, J; Ovdat, T; Zwas, D R; Fluk Gmach, S; Beigel, R; Eisen, A
Abstract: Background: Obesity is a major epidemic which is associated with major cardiovascular (CV) risk factors. Nevertheless, substantial data, mostly published more than a decade ago, have demonstrated an obesity paradox, where obese patients generally have a better short- and long-term prognosis than do their leaner counterparts with the same CV profile. As for the obesity paradox in acute coronary syndrome (ACS), prior studies demonstrated that the body-mass index (BMI)-mortality association followed a "U" shape curve: it is the highest in underweight (BMI<19) or severely obese (BMI >44), and is the lowest in overweight or mildly obese patients (BMI 30–34 and BMI 35–39) [1–2]. It is not fully elucidated whether the obesity paradox is still relevant in the current era in patients with ACS. We aimed to examine temporal trends in the clinical outcomes of ACS patients by their BMI status. Methods: Data from the ACSIS registry including all patients with calculated BMI data between the years 2000–2018. Patients were stratified by BMI groups to underweight, normal, overweight and obese. Clinical endpoints included 30d MACE, and 1-year mortality. Temporal trends were examined in the late (2010–2018) vs. the early period (2000–2008). Multivariable models examined factors associated with clinical outcomes by BMI status. Results: Among the 13, 816 patients from the ACSIS registry with available BMI data, 104 were underweight, 3921 were normal, 6224 were overweight and 3567 were obese. 1-year mortality was highest among underweight patients (24.8%), as compared to normal weight patients (10.7%) and lowest among overweight and obese patients (7.1% and 7.5% respectively; p for trend <0.001) [Figure 1]. 30-day MACE rates were qualitatively similar (24.3% for underweight, 13.6% for normal weight, 11.6% for overweight, and 11.7% for obese; p for trend<0.001). Comparing the 2 time-periods, 30-day MACE was significantly lower in the late period in all BMI groups, excluding patients who were underweight. Similarly, 1-year mortality has not changed during the years in underweight patients, and has decreased in normal weight and obese patients. Conclusions: In ACS patients, during 2-decades, 30-day MACE and 1-year mortality were lower among overweight and obese patients compared with underweight and normal weight patients. During time, 30-day MACE and 1-year mortality have decreased among the majority of BMI groups, excluding the underweight patients, in which the rates were consistently high. Our findings suggest that the obesity paradox is still relevant in ACS patients in the current era. Funding Acknowledgement: Type of funding sources: None.